Large Fermi‐Energy Shift and Suppression of Trivial Surface States in NbP Weyl Semimetal Thin Films. Issue 21 (4th May 2021) - Bedoya‐Pinto, Amilcar; Liu, Defa; Tan, Hengxin; Pandeya, Avanindra Kumar; Chang, Kai; Zhang, Jibo; Parkin, Stuart S. P.
Abstract: Weyl semimetals, a class of 3D topological materials, exhibit a unique electronic structure featuring linear band crossings and disjoint surface states (Fermi‐arcs). While first demonstrations of topologically driven phenomena have been realized in bulk crystals, efficient routes to control the electronic structure have remained largely unexplored. Here, a dramatic modification of the electronic structure in epitaxially grown NbP Weyl semimetal thin films is reported, using in situ surface engineering and chemical doping strategies that do not alter the NbP lattice structure and symmetry, retaining its topological nature. Through the preparation of a dangling‐bond‐free, P‐terminated surface which manifests in a surface reconstruction, all the well‐known trivial surface states of NbP are fully suppressed, resulting in a purely topological Fermi‐arc dispersion. In addition, a substantial Fermi‐energy shift from −0.2 to 0.3 eV across the Weyl points is achieved by surface chemical doping, unlocking access to the hitherto unexplored n‐type region of the Weyl spectrum. These findings constitute a milestone toward surface‐state and Fermi‐level engineering of topological bands in Weyl semimetals, and, while there are still challenges in minimizing doping‐driven disorder and grain boundary density in the films, they do represent a major advance to realize device heterostructures based on Weyl physics. Abstract : Topological materials host both topological (TP) and trivial (TR) surface states in their band structure, the latter being undesired for topology‐driven applications. A full suppression of trivial surface states is achieved by surface reconstruction of epitaxial NbP Weyl semimetal thin films. Moreover, large shifts of the chemical potential are induced by doping, enabling Fermi‐level engineering of purely topological states.